CRISPR/Cas9-Mediated Treatment Ameliorates the Phenotype of the Epidermolytic Palmoplantar Keratoderma-like Mouse - Xiao-Rui Luan; Xiao-Ling Chen; Yue-Xiao Tang; Jin-Yan Zhang; Xiang Gao; Hai-Ping Ke; Zhao-Yu Lin; Xian-Ning Zhang (Elsevier, 2018)
CRISPR/Cas9 has been confirmed as a distinctly efficient, simple-to-configure, highly specific genome-editing tool that has been used to treat monogenetic disorders. Epidermolytic palmoplantar keratoderma (EPPK) is a common autosomal dominant keratin disease resulting from dominant-negative mutation of the KRT9 gene, and it has no effective therapy. We performed CRISPR/Cas9-mediated treatment on a knockin (KI) transgenic mouse model that carried a small indel heterozygous mutation of Krt9, c.434delAinsGGCT (p.Tyr144delinsTrpLeu), which caused a humanized EPPK-like phenotype. The mutation within exon 1 of Krt9 generated a novel protospacer adjacent motif site, TGG, for Cas9 recognition and cutting. By delivering lentivirus vectors (LVs) encoding single-guide RNAs (sgRNAs) and Cas9 that targeted Krt9 sequence into HeLa cells engineered to constitutively express wild-type and mutant keratin 9 (K9), we found the sgRNA was highly effective in reducing expression of the mutant K9 protein in vitro. We injected the LV into the fore-paws of adult KI-Krt9 mice three times every 8 days and found that the expression of K9 decreased ∼14.6%. The phenotypic mitigation was revealed by restoration of the abnormal differentiation and aberrant proliferation of the epidermis. Our data are the first to show that CRISPR/Cas9 is a potentially powerful therapeutic option for EPPK and other PPK subtypes. Keywords: CRISPR/Cas9, gene therapy, epidermolytic palmoplantar keratoderma, Krt9 gene (mouse), indel